Stability analysis of Uçar prototype delayed system. Issue 4 (April 2016) - Bhalekar, Sachin
Abstract A simple first-order differential equation involving delay proposed by Uçar is enriched with dynamical properties. The chaotic attractors are observed in this system for some values of delay. In this paper, we propose the stability results for this delayed system for arbitrary values of parameters using the method of critical curves. We discuss the effect of each parameter on stability and hence on the chaotic behavior. Our results are confirmed by the numerical observations available in the literature.